NOMENCLATURAL STUDY OF TETRASTIGMA LEUCOSTAPHYLUM AND TETRASTIGMA RAFFLESIAE (VITACEAE): TWO COMMON HOSTS OF RAFFLESIA IN SUMATRA - Yeni Rahayu; Tatik Chikamawati; Elizabeth A. Widjaja (REINWARDTIA, 2018)
RAHAYU, Y., CHIKMAWATI, T. & WIDJAJA, E. A. 2018. Nomenclatural study of Tetrastigma leucostaphylum and Tetrastigma rafflesiae (Vitaceae): two common hosts of Rafflesia in Sumatra. Reinwardtia 17(1): 59–66. – A study of Tetrastigma (Miq.) Planch. (Vitaceae) conducted in Sumatra has revealed a number of species records. There are two species were misinterpreted. Two species names are here discussed: T. leucostaphylum (Dennst.) Alston ex Mabb. and T. rafflesiae (Miq.) Planch., which formerly united with T. lanceolarium.